The Role of Supervision of the Captain in Handling Conflicts from the Pekon Kresnomulyo Apparatus, Ambarawa District, Pringsewu District, 2023 - Ila Mei Idayanti; Eny Inti Suryani; Yonnawati Yonnawati (Penerbit Jurnal Indonesia, 2024)
Effective supervision by a sub-district head is an important element in improving and maintaining the quality of public services at the regional level. This research explores the important role played by a sub-district head in the context of supervision, focusing on their efforts in ensuring the implementation of government policies, and shows that the sub-district head's supervisory role is not only limited to routine monitoring, but also involves coordination with various parties, policy advocacy, and proactive approach to problems as they arise. Conflict management is an important aspect in maintaining social stability at the local and national level. Conflict is an inevitable phenomenon in people's lives. including in Pekon Kresnomulyo. Conflict management is important to ensure security, order and justice at the local level. One of the key figures in handling conflict is the sub-district head, who has an important role in monitoring and resolving conflicts in Pekon Kresnomulyo. This study aims to dig deeper into the role of Carnat supervision in handling conflicts in the region. The research method used is qualitative with data collection techniques through in-depth interviews and participant observation. The research results tell that the sub-district head has a significant role in monitoring, identifying and resolving conflicts that arise in Pekon Kresnomulyo. This role includes monitoring the social dynamics of society, facilitating dialogue between parties involved in the conflict, as well as collaborating with various related agencies to achieve a just and sustainable solution. However, challenges such as limited resources and the complexity of conflict often become obstacles in implementing the sub-district head's role. Therefore, synergy is needed between the sub-district head, the community and other related parties to increase the effectiveness of conflict handling in Pekon Kresnomulyo.